Endurance training: is it bad for you?. Issue 2 (June 2016) - Morici, Giuseppe; Gruttad'Auria, Claudia I.; Baiamonte, Pierpaolo; Mazzuca, Emilia; Castrogiovanni, Alessandra; Bonsignore, Maria R.
Educational aims: To illustrate the characteristics of endurance exercise training and its positive effects on health. To provide an overview on the effects of endurance training on airway cells and bronchial reactivity. To summarise the current knowledge on respiratory health problems in elite athletes. : Endurance exercise training exerts many positive effects on health, including improved metabolism, reduction of cardiovascular risk, and reduced all-cause and cardiovascular mortality. Intense endurance exercise causes mild epithelial injury and inflammation in the airways, but does not appear to exert detrimental effects on respiratory health or bronchial reactivity in recreational/non-elite athletes. Conversely, elite athletes of both summer and winter sports show increased susceptibility to development of asthma, possibly related to environmental exposures to allergens or poor conditioning of inspired air, so that a distinct phenotype of "sports asthma" has been proposed to characterise such athletes, who more often practise aquatic and winter sports. Overall, endurance training is good for health but may become deleterious when performed at high intensity or volume. Endurance training is good for health but may become deleterious when performed at high intensity or volume http://ow.ly/4n9jR4